Assessment of Knowledge, Awareness and Attitudes about the Risk of Periodontal Disease among Polycystic Ovarian Disease Patients Residing in Chennai, India: A Questionnaire based Cross-sectional Study - S Varsha; Jai Santhosh Manikandan; Makesh Raj; Sai Krishna; Hemalatha; Nanda Kumar; Pravina Fernando (Journal of Clinical and Diagnostic Research)
Introduction: Polycystic Ovarian Disease (PCOD) has become one of the most prevalent conditions among females of reproductive age. Women with PCOD are at an increased risk of developing Periodontal Disease (PD). As PD may potentially lead to tooth loss, it is essential to create active awareness. Understanding the current levels of awareness among the public would help in formulating appropriate awareness protocols. Aim: To assess the knowledge, awareness and attitudes about the risk of PD among PCOD patients residing in Chennai. Materials and Methods: A descriptive cross-sectional survey was conducted in the Department of Oral Pathology at Tagore Dental College, Chennai, Tamil Nadu, India, from December 2022 to March 2023 with 375 female participants diagnosed with PCOD and living in Chennai. Purposive sampling was employed to select participants. Data were collected using both online and offline questionnaires over a study duration of five months after obtaining informed consent. The questions assessed the knowledge, awareness and attitudes regarding the risk of PD among PCOD patients. Data were collected using Excel and transferred to the Statistical Package for the Social Sciences (SPSS) version 24.0 for analysis. Categorical data were expressed in frequencies and percentages. Results: The study revealed that PCOD patients aged from 15 to 46 years, with a mean age of 22.25±5.03 years. Of the participants, 82.9% brushed their teeth once a day and 78.6% never flossed their teeth, indicating poor oral hygiene practices. Out of the 53 (14.1%) of participants who were aware that PCOD can affect oral health, about 29.3% received this information from their dentists and 26.8% received it from the internet. Approximately 93.6% of PCOD patients were not aware of the increased risk of PD due to PCOD and the majority (90.7%) did not believe they needed more frequent dental visits than non PCOD females, indicating relatively limited knowledge about the potential oral complications of PCOD. However, 97.1% of participants demonstrated a positive attitude toward adopting preventive measures to prevent PD/gum disease related to PCOD in the future. Conclusion: The results of the present study highlight significant gaps in the knowledge, awareness and attitudes regarding the risk of PD among women with PCOD in Chennai. The key findings indicate that while there is a general lack of awareness about the association between PCOD and PD, there is a notable positive attitude toward adopting preventive measures for oral health. There is a critical need to create awareness among women with PCOD regarding the risk of PD to improve their quality of life.